(untitled) (Foro de Educacion, 2024)
Especially the mission to educate to our minors and young people falls, directly, on two essential pillars: the family and the school. Although in the family the essential figure that is going to carry out educative and social the workings is the parents; in the case of the school, the subject key of formation is the teaching staff. In order to be able to analyze the situation that the educational ones are living at present, it is precise that we realise an approach to the essential functions that is to ful- fils and that it develops at present, as well as similarly it is precise that we pay a special attention to those factors that of a way or another one are conditioning the educa- tional practice and bursting in into the good development of the formation. But we do not have to forget that the educational one is not a mere transmitter of knowledge, but also that is a strong socializing agent and who, through its teaching, transmits a series of values that are going to pierce, directly or indirectly, in the forma- tion of youngest.